New equations of infinitesimal deformations of surfaces in $E_3$ - Potapenko, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We establish a condition for two symmetric tensor fields that is necessary and sufficient for the existence of a displacement vector in the case of infinitesimal deformation of a surface in the Euclidean space E 3.